Identity of the Malay and Nusantara Islam Society: An Analysis Through Yusuf al-Qaradawi's Islamic Transformation Thought - Otoman Otoman; Duski Ibrahim; Endang Rochmiatun (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
This article explores the identity of the Malay and Nusantara Muslim societies by analyzing the transformative Islamic thought of Yusuf Al-Qaradawi. Al-Qaradawi’s approach to Islamic reform emphasizes the need to contextualize Islamic teachings, offering a flexible and dynamic interpretation of the faith that aligns with the realities of modern societies. In the context of Malay and Nusantara Islam, this article delved into the interaction between traditional Islamic values, indigenous cultures, and the challenges posed by globalization and modernity. The analysis employs a qualitative research methodology, using a comprehensive literature review of primary sources, such as Al-Qaradawi’s key works on Islamic reform and his commentaries on contemporary Islamic issues. Secondary sources, including scholarly articles and books on Malay and Nusantara Islam, are also analyzed to provide a broader context for his influence in the region. A thematic analysis of key concepts, such as ijtihad (independent reasoning), reform, and the intersection of Islamic teachings with modern social and political realities, forms the backbone of the study. This methodology allows for a critical evaluation of how Al-Qaradawi’s thought contributes to the shaping of Islamic identity in the Malay Archipelago, offering both theoretical and practical insights into the relevance of his ideas for contemporary Muslim societies.